Beispiel Nr: 09
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ -\frac{1}{2} x +1 y =2\\ \frac{1}{2} x -3 y = -3 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} I \qquad -\frac{1}{2} x +1 y =2\\ II \qquad \frac{1}{2} x -3 y = -3 \\ \text{I nach y auflösen}\\ -\frac{1}{2} x +1 y =2 \\ -\frac{1}{2} x +1 y =2 \qquad /+\frac{1}{2} x\\ 1 y =2 +\frac{1}{2} x \qquad /:1 \\ y =2 +\frac{1}{2} x \\ \text{II nach y auflösen}\\ \frac{1}{2} x -3 y =-3 \\ \frac{1}{2} x -3 y =-3 \qquad /-\frac{1}{2} x\\ -3 y =-3 -\frac{1}{2} x \qquad /:\left(-3\right) \\ y =1 +\frac{1}{6} x \\ \text{I = II}\\ 2 +\frac{1}{2} x =1 +\frac{1}{6} x \qquad /-\frac{1}{2} x /-1 \\ 2-1 =\frac{1}{6} x -\frac{1}{2} x \\ 1 =-\frac{1}{3} x \qquad /:\left(-\frac{1}{3}\right) \\ x=-3 \\ \text{x in I}\\ y =2 +\frac{1}{2} \cdot -3 \\ y=\frac{1}{2} \\ L=\{-3/\frac{1}{2}\} \end{array} & \begin{array}{l} I \qquad -\frac{1}{2} x +1 y =2\\ II \qquad \frac{1}{2} x -3 y = -3 \\ \text{I nach x auflösen}\\ -\frac{1}{2} x +1 y =2 \\ -\frac{1}{2} x +1 y =2 \qquad /-1 y\\ -\frac{1}{2} x =2 -1 y \qquad /:\left(-\frac{1}{2}\right) \\ x =-4 +2 y \\ \text{II nach x auflösen}\\ \frac{1}{2} x -3 y =-3 \\ \frac{1}{2} x -3 y =-3 \qquad /+3 y\\ \frac{1}{2} x =-3 +3 y \qquad /:\frac{1}{2} \\ x =-6 +6 y \\ \text{I = II}\\ -4 +2 y =-6 +6 y \qquad /-2 y /+6 \\ -4+6 =6 y -2 y \\ 2 =4 y \qquad /:4 \\ y=\frac{1}{2} \\ \text{y in I}\\ x =-4 +2 \cdot \frac{1}{2} \\ x=-3 \\ L=\{-3/\frac{1}{2}\} \end{array} \end{array} $